Writing (in) Love: Goethe's 'Buch Suleika' and the Biblical Song of Songs. (2nd September 2018) - Sauter, Caroline
ABSTRACT: This essay demonstrates that the creation of a poetic language of love in the West-östlicher Divan is deeply rooted in a specific tradition within Western intellectual history that Goethe had actively engaged with in his early work, and that was vehemently discussed during his lifetime: namely, the translation, adaptation, and interpretation of the biblical Song of Songs ( Hohes Lied ). More specifically, I claim that the Song provides the model for the poetic language of love that Goethe develops in the 'Buch Suleika', a language which is understandable on at least two levels — on a public level, as orientalist poetry by one of the most eminent poets of his epoch, and on a deeply personal level, as a mutual declaration and confession of love.